Implementation of pharmacotherapy guidelines in heart failure: experience from the German Competence Network Heart Failure - Zugck, Christian; Franke, Jennifer; Frankenstein, Lutz; Scheffold, Thomas; Katus, Hugo (Clinical research in cardiology, 2012)
AimTo evaluate the implementation of current pharmacotherapy guidelines of heart failure and to identify factors associated with high pharmacotherapy guideline adherence in heart failure patients.Methods and resultsWe pooled data from seven studies performed in the context of the German Competence Network Heart Failure selecting patients with chronic systolic heart failure and left ventricular ejection fraction (LVEF) <45% (n = 2,682). The quality of pharmacotherapy was evaluated by calculating the guideline adherence indicator (GAI), which considers three (GAI-3) or five (GAI-5) of the recommended heart failure substance classes and accounts for respective contraindications. GAI-3 was categorized as perfect (GAI = 100%: 71% of the cohort), medium (GAI = 50-99%: 22%), and poor adherence (GAI <50%: 7%). In ordinal regression, the following factors were positively associated with perfect adherence: history of revascularization (odds ratio 1.59, 95% confidence interval 1.27-1.98), prior ICD implantation (2.29, 1.76-2.98), and LV ejection fraction <30% (1.45, 1.19-1.76), whereas age (per 10 years; 0.82, 0.77-0.89), NYHA III/IV (0.15, 0.12-0.18), unknown duration of heart failure (0.69, 0.53-0.89), and antidepressant medication (0.61, 0.42-0.88) were negatively associated with perfect adherence. Better GAI-3 at baseline predicted favorable changes of LV ejection fraction and end-diastolic diameter after 1 year. One-year mortality risk was closely related to GAI-3 in both groups of NYHA functional class I/II (excellent vs. poor GAI-3: 7.2 vs. 14.5%, log rank = 0.004) and class III/IV (13.5 vs. 21.5%, log rank = 0.005).ConclusionsThis large pooled analysis showed that a high level of guideline adherence is achievable in the context of clinical studies. Those receiving and tolerating optimal pharmacotherapy experience a better prognosis. Nevertheless, the implementation of heart failure medication needs further improvement in female and elderly patients, especially those in NYHA functional class >II and patients with LVEF ≥30%.